2017
DOI: 10.2174/1567205014666170417110337
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mononuclear Cells of Alzheimer's Disease Patients Control CCL4 and CXCL10 Levels in a Human Blood Brain Barrier Model

Abstract: These findings highlight the interest of a BBB model in order to explore chemokine production. For the first time, results showed that PBMCs from patients with AD can control the production of CCL4 and CXCL10 in a human BBB model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…Studies analysing the chemotactic crosstalk occurring at the BBB between peripheral cells, actors of the BBB and the parenchyma brain during AD are lacking. We conducted a previous study in order to analyse the production of five chemokines known to be implicated in the pathogenesis of AD in a human BBB model, and also to assess whether PBMCs from AD patients could impact chemokine production [ 35 ]. This work showed that BBB models are valuable tools to explore chemokine production and that PBMCs from AD patients at a moderate stage could influence CCL4 and CXCL10 production in this human BBB model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies analysing the chemotactic crosstalk occurring at the BBB between peripheral cells, actors of the BBB and the parenchyma brain during AD are lacking. We conducted a previous study in order to analyse the production of five chemokines known to be implicated in the pathogenesis of AD in a human BBB model, and also to assess whether PBMCs from AD patients could impact chemokine production [ 35 ]. This work showed that BBB models are valuable tools to explore chemokine production and that PBMCs from AD patients at a moderate stage could influence CCL4 and CXCL10 production in this human BBB model.…”
Section: Discussionmentioning
confidence: 99%
“…Blood sample were transferred into 10 mL BD Vacutainer ® tube. Then, PBMCs were isolated using a Ficoll Histopaque-1077 density gradient and cultured as previously described [ 27 , 28 ]. PBMCs were seeded at 500,000 cells/500 μL of complete culture medium (RPMI 1640 medium completed with 10% of newborn calf serum, 1% of PS and 10% of PHA at 20 μg/mL) in 12-well plates for 24 hours, and then transferred in the upper side of insert of the BBB model in direct contact with hCMEC/D3 cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations